Pengaruh Profesionalisme, Independensi, Etika Profesi, Skeptisme Profesional dan Fee Audit terhadap Kualitas Audit pada KAP di Kota Padang - Berlianna Sya’Bani Harneli; Rahmaita (CV. ITTC INDONESIA, 2024)
The purpose of this study was to analyze the effect of professionalism, independence, professional ethics, auditor skepticism and audit fees on audit quality at the hood in Padang City. This type of research is quantitative research, using primary data in the form of questionnaires distributed directly to Public Accounting Firms in Padang City. The population used in this study are auditors who work at the Padang City Public Accounting Firm (KAP) which is officially registered with the Indonesian Public Accountants Association (IAPI) in 2023. In this study, the sample was determined using purposive sampling technique. Data analysis methods using Descriptive Statistical Analysis and data quality tests. Based on the research results, the following five things are concluded. First, the findings of the research results explain the independent variable, namely professionalism, has a t count of 4.601> t table 2.010 with a significance value of 0.000 <0.05. So that it explains that the professionalism variable has a significant positive effect on Audit Quality. Second, the findings of the research results explain that the independent variable, namely independence, has a t count of 2.917> t table 2.010 with a significance value of 0.005 <0.05. So that it explains that the Independence variable has a significant positive effect on Audit Quality. Third, the findings of the research results explain that the independent variable, namely Professional Ethics, has a t count of 2.995> from t table 2.010 with a significance value of 0.004 < 0.05. So that it explains that the Professional Ethics variable has a significant positive effect on Audit Quality. Fourth, the findings of the research results explain that the independent variable, namely Professional Skepticism, has a t count of 1.493 < from the t table 2.010 with a significance value of 0.142> 0.05. So that it explains that the Professional Skepticism variable has no significant effect on Audit Quality. Fifth, the findings of the research results explain that the independent variable, namely the Audit Fee, has a t count of -0.577 < from the t table 2.010 with a significance value of 0.566> 0.05. So that it explains that the Audit Fee variable has no significant effect on Audit Quality